Simulation and experimental study on the use of shaped charge jet as transient antennas for radiating electromagnetic pulses - Jiahui Guo; Bin Ma; Zhengxiang Huang; Yong Peng; Xin Jia (Defence Technology)
In this study, the potential application of shaped charge jets as transient antennas for electromagnetic signal transmission was explored and an electromagnetic pulse radiation system with a shaped charge jet as a transient antenna was proposed. During the research, crucial characteristics of the transient antenna formed by a shaped charge with a 30 mm diameter, such as resonant frequency, radiation pattern, and radiation efficiency, were evaluated. The typical shaped charge jet morphology was obtained based on the simulations, in which it could insight the dynamic behavior of the shaped charge jet selected. An equivalent model experiment was employed to test the radiation efficiency, and it showed that a shorting pin loading method could increase the relative bandwidth of the jet antenna to 32.8%, and the experimental results correlate with the theoretical predictions for half-wave dipole antennas reasonably well. Additionally, variations in the diameter of the shaped charge jet were found to affect the input impedance and impedance bandwidth, while the length of the jet influenced the resonant frequency of the antenna. This suggests that altering these parameters can achieve reconfigurability of the jet antenna.